(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The cold temper rolling process is one of the last steps on the production of thin strips, and has many purposes. It is characterized for the low reduction applied on the strip, usually of the order of 0.5 5%. Temper rolling is used to improve the final flatness of the strip and its metallurgical properties, eliminate upper and lower yield stress behavior, achieve a better surface finishing and, sometimes, induce magnetic properties. The conditions in the roll bite are different from other kinds of cold rolling in reversible and tandem rolling mills. As was mentioned before, the reduction is very low, the deformation of the roll is very localized in the arc of contact area and there is considerable elastic spring back of the strip. These differences make the calculation of the rolling load very difficult. Furthermore there is lack of information of the process that show the need for a deeper research on the subject of the temper rolling process of metal strips. In this work the temper rolling process is modelled with the elastoplastic finite element method, dynamic explicit, in the plane strain state in order to a better understanding of the process. Modelling details are also given.